High-Frequency Oscillation of the Active-Bridge-Transformer-Based DC/DC Converter - Shusheng Wei; Wusong Wen (Energies, 2022)
The dual-active-bridge converter (DAB) has attracted tremendous attention in recent years. However, its EMI issues, especially the high-frequency oscillation (HFO) induced by the dv/dt and parasitic elements of the transformer, are significant challenges. The multi-active-bridge converter (MAB) based on the multi-winding transformer also faces similar problems, which are even more complicated. This article investigates the HFO of active-bridge-transformer-based DC/DC converters including DAB and MAB. Firstly, the general HFO model is studied using the analysis of the AC equivalent circuit considering the asymmetrical parameters. Ignoring the AC resistance in the circuit, the high-order model of the voltage oscillation could be reduced to a second-order system. Based on the simplified model, the oscillation voltage generated by an active bridge is analyzed in the time domain. Then, a universal active voltage-oscillation-suppression method-selected harmonic-elimination phase-shift (SHE PS) modulation method is proposed. The impacts of the system parameters on the method are also revealed. The experimental results show the excellent performance of the proposed active suppression method, with voltage spike amplitude (VSA) reductions of 92.1% and 77.8% for the DAB and MAB prototypes, respectively.